2009
DOI: 10.1534/genetics.109.104737
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Isolation of the M Gene Suggests That a Conserved-Residue Conversion Induces the Formation of Bisexual Flowers in Cucumber Plants

Abstract: Sex determination in plants involves a variety of mechanisms. Here, we report the map-based cloning and characterization of the unisexual-flower-controlling gene M. M was identified as a previously characterized putative 1-aminocyclopropane-1-carboxylic acid synthase gene, while the m allele that mutated at a conserved site (Gly33Cys) lost activity in the original enzymatically active allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 27 publications
4
124
0
1
Order By: Relevance
“…Recently, Boualem et al (2008) and Li et al (2009) reported that mutation of a melon and cucumber ACS isogene (CmACS-7 and CsACS2, respectively) resulted in the transition from monoecy to andromonoecy. Thus, CmACS-7 (Boualem et al, 2008) and CsACS2 (Boualem et al, 2009;Li et al, 2009) repress stamen development in female flowers. CmACS-7 and CsACS2 are also members of the type 3 ACS isozyme subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Boualem et al (2008) and Li et al (2009) reported that mutation of a melon and cucumber ACS isogene (CmACS-7 and CsACS2, respectively) resulted in the transition from monoecy to andromonoecy. Thus, CmACS-7 (Boualem et al, 2008) and CsACS2 (Boualem et al, 2009;Li et al, 2009) repress stamen development in female flowers. CmACS-7 and CsACS2 are also members of the type 3 ACS isozyme subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Cucurbits are becoming primary models for the study of several biological processes (Boualem et al 2008;Ezura and Fukino 2009;Li et al 2009). The availability of molecular tools, including the whole genome sequence, has significantly increased in the last years, mainly for melon and cucumber (Huang et al 2009;Gonzalez et al 2010), but more recently also for the Cucurbita genus.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of molecular tools, including the whole genome sequence, has significantly increased in the last years, mainly for melon and cucumber (Huang et al 2009;Gonzalez et al 2010), but more recently also for the Cucurbita genus. Gong et al (2008) developed the first collection of genomic SSRs (gSSR), about 400, using an enriched genomic library from an oil-seed Pumpkin cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, stamen development is regulated by ethylene derived from the CS-ACS2 gene in cucumber plants ( Fig. 1A; Boualem et al, 2009;Li et al, 2009). Because the amino acid sequences of CmACS-7 and CS-ACS2 show a high degree of similarity (98%) (Boualem et al, 2008(Boualem et al, , 2009Li et al, 2009), these genes are homologs in Cucumis plants.…”
Section: Discussionmentioning
confidence: 95%
“…Yamasaki et al (2003b) also showed the possibility that the expression of the CS-ACS2 gene is regulated by M protein under short-day conditions. Recently, the CS-ACS2 gene was identified as the M gene (Boualem et al, 2009;Li et al, 2009); thus, both F and M genes encode ACC synthase in cucumber. Based on these reports, our genetic model of sex expression in cucumber plants can be modified as shown in Figure 1A.…”
Section: Introductionmentioning
confidence: 99%